Optimalisasi Sistem Informasi Untuk Efektifitas Program Kerja Pengawasan Tahunan (PKPT) Inspektorat Kabupaten Bondowoso - Lukman Fakih Lidimilah; Jarot Dwi Prasetyo; Ahmad Homaidi (Department of Science and Technology Ibrahimy University, 2020)
The preparation of an annual supervisory work program (PKPT) requires a long process in order to get good and accurate results, because the process is done semi-computerized, which still involves a lot of staff in the Inspectorate. This makes the PKPT formulation process less effective and efficient. So that the supervisory work program that should have been able to be carried out quickly became constrained because of the long process in its preparation. Therefore, it is deemed necessary to design an application that can help facilitate the preparation of an annual monitoring work program with the waterfall method, making it easier for the inspectorate to determine audit objects and the implementation of supervision of predetermined objects. Based on the tests carried out, it was found that the application feasibility was 93%. From the results of these tests, this application can help make it easier for the inspectorate to provide an assessment of the level of risk, determine supervision plans and assignments to be more effective and efficient. So that efforts to become Good Governance and Clean Governance can be realized properly.